Effect of Replacing Conventional Base Materials with Granular Volcanic Ash on Engineering Properties - Saddam H. Alhadama; Abdullah A. Almaswari; Ziyad M. Algaboby (University of Science and Technology, Sana'a, Yemen, 2023)
Granular Volcanic Ash (GVA) is a material of volcanic activity; it has a rough surface, a low specific gravity, and a high porosity because of the structures of the minerals in it. The purpose of this study was to find a way to utilize this waste material, which is widely distributed across Yemen, by using GVA for the placement of conventional coarse aggregate (basalt aggregate) while constructing roads. In this study, Red and Black GVA materials were combined with conventional coarse aggregate for use in the construction of pavement. Base coarse materials were blended with GVA aggregate and examined for their engineering characteristics in an experimental study. Conventional coarse aggregate was partially replaced by five replacement levels from GVA, corresponding to 10%, 20%, 30%, 40%, and 50% of the dry aggregate's total weight, were applied. As a control, a sample with no volcanic ash had been used. According to the results of experiment tests includes: density, California bearing ratio (CBR), abrasion percentage, and permeability test, it is possible to replace some of the basalt aggregates with GVA. Results showed that the engineering properties of base coarse materials specifications for CBR, and abrasion percentage were satisfied for volcanic ash percentages up to 20%.